2001
DOI: 10.1051/0004-6361:20011173
|View full text |Cite
|
Sign up to set email alerts
|

The self-enrichment of galactic halo globular clusters

Abstract: Abstract.We discuss the existence of a mass-metallicity relation among galactic halo globular clusters. The lack of any luminosity-metallicity correlation in globular cluster systems has been used as an argument against self-enrichment models of cluster formation. We show that such a relation is statistically present among the galactic Old Halo globulars. This observational correlation implies that the least massive old clusters are the most metal-rich. This is in contradiction with the idea that, if globular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…(1999), proto-GC clouds are confined by a hot protogalactic medium, and this model in fact predicts an inverse GC mass-metallicity relation, in which the most massive GCs are the most metal-poor (Parmentier & Gilmore 2001).…”
Section: The Blue Tiltmentioning
confidence: 97%
“…(1999), proto-GC clouds are confined by a hot protogalactic medium, and this model in fact predicts an inverse GC mass-metallicity relation, in which the most massive GCs are the most metal-poor (Parmentier & Gilmore 2001).…”
Section: The Blue Tiltmentioning
confidence: 97%
“…This is true for any cluster system characterised by a stellar IMF that is invariant, and if the cluster age range is a limited fraction of the mean age of the cluster population. As regards the old GCs in the Galactic halo, the range spanned by their visual M/L ratio is limited (i.e., Pryor & Meylan 1993; see also Parmentier & Gilmore 2001, their fig. 1), and the scatter partly reflects variations in the dynamical evolution of individual GCs.…”
Section: Old Globular Clustersmentioning
confidence: 99%
“…8, which shows a small trend of [Ca/Fe] with metallicity. Indeed, Parmentier & Gilmore (2001), who studied the chemical enrichment of PGCCs with varying initial mass, predict that, the more massive the PGCCs, the lower the [Fe/H] achieved. Our modified EASE scenario, in which the most massive PGCCs would produce the highest [α/Fe] and the lowest [Fe/H], could therefore explain the small trend with metallicity which is observed in Fig.…”
Section: Modified Ease Scenariomentioning
confidence: 99%
“…taken place in the GC where the stars were born, that is, the more efficient the accretion process, the larger the [Y/Fe] ratio. This EASE scenario (standing for Evaporation/ Accretion/Self-Enrichment), which was devised to interpret the observed abundance correlations, subsequently proved to be able to explain the observed metallicities of present-day Galactic halo GCs (Parmentier et al 1999) as well as the distance-metallicity relation for the subgroup of Galactic GCs belonging to the Old Halo (Parmentier et al 2000) and the mass-metallicity relation found for the same subgroup (Parmentier & Gilmore 2001).…”
Section: Introductionmentioning
confidence: 99%